1989
DOI: 10.1128/jvi.63.5.1938-1944.1989
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virus-specific RNA-dependent RNA polymerase activity in extracts from cells infected with lymphocytic choriomeningitis virus: in vitro synthesis of full-length viral RNA species

Abstract: We have developed an in vitro assay for the lymphocytic choriomeningitis virus (LCMV) RNA-dependent RNA polymerase with ribonucleoprotein complexes extracted from acutely infected tissue culture cells. The RNA products synthesized in vitro corresponded in size to the full-length genomic L and S RNAs and subgenomic NP and GP mRNAs normally produced in vivo during acute LCMV infection. In a temporal analysis spanning the first 72 h of acute infection, the in vitro polymerase activity of ribonucleoprotein complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…To examine both genome replication and transcription if possible, we used cytoplasmic extracts of infected cells rather than purified virions. Moreover, an in vitro system in which lymphocytic choriomeningitis virus RNA was synthesized from intracellular nucleocapsids (NCs) had previously been reported (5). To examine the de novo-made RNAs, the reaction mixtures were labelled with [32P]UTP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine both genome replication and transcription if possible, we used cytoplasmic extracts of infected cells rather than purified virions. Moreover, an in vitro system in which lymphocytic choriomeningitis virus RNA was synthesized from intracellular nucleocapsids (NCs) had previously been reported (5). To examine the de novo-made RNAs, the reaction mixtures were labelled with [32P]UTP.…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION Because of the unusual 5' ends of the TAC RNAs found in vivo, we have examined viral RNA synthesis in vitro. Using NCs from lymphocytic choriomeningitis virus-infected cells, Fuller-Pace and Southern (5) had previously reported that genomes as well as mRNAs were made. We found this surprising, as their NCs were treated with high salt and detergent before being pelleted through a 50% sucrose cushion and so should be free of a soluble pool of N protein thought to be required to support genome replication.…”
Section: Vol 66 1992mentioning
confidence: 99%
“…L protein mediates the synthesis of two RNA species: mRNA terminating in the intergenic region and noncapped genomic or antigenomic RNA representing a full-length copy of the genome (10,35). The central domain of the protein from amino acid residues 1000 to 1500 harbors the RNA-dependent RNA polymerase (RdRp) (8,11,19,29,47). Enzymatic functions residing in the N terminus and C terminus of the L protein are unknown.…”
mentioning
confidence: 99%
“…For most or all positive-strand RNA viruses of eukaryotes examined to date, the viral RNA-dependent RNA replication complex copurifies with membrane extracts from infected cells (4,11,16,21,45,46,55). In some cases, negative-strand RNA synthesis activity can be solubilized from such membrane extracts (55,64), but in vitro studies with positive-strand RNA viruses as varied as picornaviruses and nodaviruses suggest that membrane association is important for synthesis of positivestrand RNA (3,47,64).…”
mentioning
confidence: 99%